2010
DOI: 10.1074/jbc.m110.161372
|View full text |Cite
|
Sign up to set email alerts
|

Joint Functions of Protein Residues and NADP(H) in Oxygen Activation by Flavin-containing Monooxygenase

Abstract: The reactivity of flavoenzymes with dioxygen is at the heart of a number of biochemical reactions with far reaching implications for cell physiology and pathology. Flavin-containing monooxygenases are an attractive model system to study flavin-mediated oxygenation. In these enzymes, the NADP(H) cofactor is essential for stabilizing the flavin intermediate, which activates dioxygen and makes it ready to react with the substrate undergoing oxygenation. Our studies combine site-directed mutagenesis with the usage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
65
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(72 citation statements)
references
References 30 publications
7
65
0
Order By: Relevance
“…The model in Fig. 8 is also supported by the recent investigation of a flavin-containing monooxygenase showing that an N78S mutant, in which the site near the C4a/N5 locus is widened and in which the H-bonding interaction between the flavin N5 and NADP ϩ is altered, voids its ability to form a C4a-hydroperoxyflavin intermediate (41).…”
Section: Discussionsupporting
confidence: 53%
“…The model in Fig. 8 is also supported by the recent investigation of a flavin-containing monooxygenase showing that an N78S mutant, in which the site near the C4a/N5 locus is widened and in which the H-bonding interaction between the flavin N5 and NADP ϩ is altered, voids its ability to form a C4a-hydroperoxyflavin intermediate (41).…”
Section: Discussionsupporting
confidence: 53%
“…2C). Since oxidized NADP + remains tightly bound and is involved in the stabilisation of the C4a-hydroperoxy-FAD intermediate that is crucial for substrate oxygenatio n (Alfieri et al, 2008;Orru et al, 2010), S195L mutation may destabilise the NADP + binding and accelerate the decay of the intermediate, which is in good agreement with the dramatically reduced kcat for TMA ( Table 2).…”
Section: Structural Mapping Of the Critical Hfmo3 Allelic Variantssupporting
confidence: 75%
“…Thus, the analog does not bind in a conformation optimal for the stabilization of the oxygenated flavin intermediates. Similar effects were observed by mutating residues that interact with the amide group of the nicotinamide ring in FMO (35). Because NADP(H) is expected to play a similar role in SidA as reported for FMO, it is reasonable to assume that a similar effect occurs in SidA.…”
Section: Discussionmentioning
confidence: 50%
“…In addition, we also showed that reduction of the flavin results in interaction of the carbonyl oxygen of the amide group of NADP ϩ with N5 of the flavin. This interaction is believed to be essential in preventing the release of hydrogen peroxide, as demonstrated in other flavin-dependent reactions (14,29,35,36).…”
Section: Discussionmentioning
confidence: 99%